Winter of the world - Follett, Ken. (New York : Dutton, 2012)
Continues the stories of five interrelated families who struggle with social, political, and economic turmoil in the mid-twentieth century, during which they witness the rise of Nazi Germany, the Spanish Civil War, and the horrors of World War II.
Maps on lining papers.
Keywords: Twentieth century -- Fiction; World War, 1939-1945 -- Fiction; Spain -- History -- Civil War, 1936-1939 -- Fiction